2020
DOI: 10.1039/c9nr09386a
|View full text |Cite
|
Sign up to set email alerts
|

Structure design and performance of photomultiplication-type organic photodetectors based on an aggregation-induced emission material

Abstract: High performance photomultiplication-type organic photodetectors based on an AIE material were successfully fabricated by designing a device structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…[35,52] The difference between J L and J d is the photogenerated current density (J ph ) for PD-OPDs, or photo-induced current density (J pi ) for PM-OPDs, which mainly originates from charge tunneling injection. [18,19,53]…”
Section: Dark Current Density and Light Current Densitymentioning
confidence: 99%
See 3 more Smart Citations
“…[35,52] The difference between J L and J d is the photogenerated current density (J ph ) for PD-OPDs, or photo-induced current density (J pi ) for PM-OPDs, which mainly originates from charge tunneling injection. [18,19,53]…”
Section: Dark Current Density and Light Current Densitymentioning
confidence: 99%
“…Besides introducing traps into active layer and interfacial layer, employing the interfacial charge blocking layer can also lead to PM phenomenon in OPDs. [36,53,[113][114][115][116] Hammond et al reported high photocurrent multiplication in broadband OPDs through tailored charge blocking layers. [113] Figure 10a illustrates the device structure of the PM-OPDs, which structured as ITO/naphthalenetetracarboxylic dianhydride (NTCDA)/C 60 /copper phthalocyanine (CuPc):C 60 (3:7, wt/wt)/BCP/Al.…”
Section: Charge Blocking Layers Based Broadband Pm-opdsmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12] Among these, photomultiplication-type OPDs (PM-OPDs) are receiving increasing attention due to their exceptionally high external quantum efficiency (EQE). [13][14][15][16][17][18] Photomultiplication is an extrinsic photocurrent amplification mechanism in which trapped charge carriers (e.g., electrons) can induce the injection of the counter charge carriers (e.g., holes) by tunneling from the external circuit, which differs from the intrinsic multiexciton generation mechanism. [19] Specifically, when slower charge carriers (e.g., electrons) are trapped in the photoactive layer, the counter charge carriers (e.g., holes) can continuously circulate the circuit until the circulating carriers are recombined with the trapped carriers.…”
Section: Introductionmentioning
confidence: 99%